Automatic Wipe And Smart Control Wiper Using Sensor And Controller System - Nor Asyikin , Abd Hamid (UTeM, 2009)
This project aims to build the automatically wiper system by using programmable software. This system functions through the combination of the hardware and software. This system is called automatic wipe and smart control wiper using sensor and controller system. The advantage of this project was help users to use the wiper automatically when the sensor detects raindrops. Driver doesn’t need to turn on or turn off the control stalk at the wiper. This system will function automatically when the raindrops. Sensor use to senses the raindrop or moisture when it hitting on sensor. Otherwise, this system function to push up and pull down the wiper when the engine was starting or engine stops. This system prevents the wiper’s rubber from damage during hot weather. The main objectives of this project are to upgrade the older cars system and to prevent the wiper’s rubber from damage. The material as a stand used to pull down the wiper when the engine is started. When the engine is stops, the wipers automatically push up using the motor placed at the wiper blade. The mechanical function is used to control the motor system. By using this system, user doesn’t control the wiper system manually and this system functions using controller system.